Presence of Tannerella forsythia in patients with chronic periodontal disease and atherosclerosis - Staletović, Danijela; Kannosh, Ibrachim; Šehalić, Meliha; Vukićević, Vladanka; Milojković, Zoraida; Ilić, Aleksandra; Pavlić, Verica; Brkić, Zlata (Vojnosanitetski pregled, 2021)
Background/Aim. Periodontal disease is an inflammatory disease that occur in the tissues surrounding the teeth in response to bacterial biofilm accumulation (dental plaque). Among others, Tannerela forsythia (Tf) was recognized as one of the most significant and specific bacterial species in periodontal pocket („red complex“ bacteria). Atherosclerosis is a progressive narrowing of arteries that may lead to occlusion, as a consequence of lipid deposition. It underlies coronary heart disease (80%), as well as myocardial and cerebral infarctions. Increasing evidence over the past decade suggests a link between periodontal disease and atherosclerosis, where Tf can enter the systemic circulation directly or indirectly, and be present in atherosclerotic blood vessels. Therefore, the aim of this study was to detect the presence of Tf in atheromatous plaques obtained from different blood vessels in patients with chronic periodontitis. Methods. Ninety patients (male 61, female 29) with periodontal disease and atherosclerosis [recruited for either carotid artery stenosis requiring endartectomy or percutaneous transluminal coronary angioplasty (PTCA)] were included in this study. Clinical periodontal examinations consisted of plaque index (PI) (according to Silness Lӧu), gingival index (GI) (according to Lӧe Silnes), sulcus bleeding index (according to Mühleman-Son) and periodontal probing depth (PPD). Presence of Tf in periodontal pockets and atherosclerotic vessels was detected using polymerase chain reaction (PCR) method with positive control Tf ATCC 43037. Results. Tf was present in subgingival plaques of 68 (75.6%) of the patients, while its presence in atheromatous plaques were registered in 42 (53.3%) of the patients. It was significantly present in coronary blood vessels (41.7%), followed by carotid arteries (35.4%) and a. abdominalis aneurism (12.5%), a. mamaria (8.5%) and a. femoralis (2.1%) while in a. iliaca Tf was not detected at all. Conclusion. The present study suggests strong relationship between periodontal inflammation and atherogenesis; therefore, it should be considered as potential risk factor for atherosclerosis. Accordingly, it would be necessary to control periodontal disease in order to reduce mortality and morbidity associated with atherosclerosis.